Caracterização da preensão de crianças típicas com idade entre 5 e 10 anos - Silva, Louise Gracelli Pereira da (Universidade Federal de São Carlos, 2015)
The grasp is recognized as a useful tool to identify the level of development and the degree of disability of an individual on clinical practice; however the data available in the literature about the maximum grip strength in children and adolescents should be periodically extended. In addition, there is no quantitative researches on literature about the pattern of development grasp of typical children. Objective: To characterize the handgrip of typical children aged between 5 and 10 years. Methods: The project was divided into two studies. On study 1, healthy children, aged between 5 and 10 years were divided into six groups according to age. Participants were subjected to a single assessment to obtain the anthropometry data (height and weight) and grip strength data (maximum grip strength). On study 2, a device was developed to characterize, both qualitatively and quantitatively, the standard grip for the task of drinking water. To test the device, they were randomly selected 16 participants from the study 1. Results:(Study 1) Significant increase in maximum grip strength throughout the ages was observed. The boys were stronger than girls. The dominant hand was stronger than the non-dominant hand for both genders. For girls, there was a strong correlation between maximum grip strength with the hand length and body mass. For boys, therewas a strong correlation with the length of the hand and height. (Study 2) The grip pattern data were measured using a device whose shape was made to a similarly transparent glass. Final Considerations: This study provides reference values for maximum grip strength of children aged between 5 and 10 years. The maximum grip strength increases throughout the ages. The boys are stronger than girls, regardless of age and tested hand. In addition, it was developed a prototype device that ultimately could providea detailed evaluation of the strategies used in the handgrip for a functional task. Thus expanding the understanding of the mechanisms related to modulation of grip when handling objects will assist in identifying the pathogenesis of motor disorders in children with developmental disorders without the values are underestimated by the expected for their age.
Keywords: Fisioterapia; Crianças; Preensão palmar; Força; Mãos; Children; Functionality; Grasp; Grip strength; Hand; Handgrip; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL